Primer on the rheumatic diseases - Klippel, John H. (Springer, 2008)
Arthritis and other rheumatic diseases are a leading cause of disability and affect more than 46 million Americans (including 300,000 children). The Primer is designed to provide up-to-date information about the major clinical syndromes, with comprehensive texts on arthritis and related diseases, including osteoarthritis, rheumatoid arthritis, osteoporosis, lupus and more than one hundred others. Color figures depict cutaneous findings and histopathology.